Recent Advances in Physical, Enzymatic, and Genetic Modifications of Starches - Bensaad, Dhiya Eddine; Saleh, Mohammed; Ismail, Khalid; Lee, Youngseung (Jordan Journal of Agricultural Sciences, 2022)
The current review presents the potential physical modification devised into thermal which includes pre-gelatinization and hydrothermal processing (i.e., annealing (ANN) and heat-moisture treatment (HMT)) and nonthermal modifications (i.e., high-pressure processing (HPP), micronization, ultrasonication, and pulsed electric field (PEF)). Rather than physical modification; enzymatic modification by single enzyme treatment, debranching enzymes, and multienzyme synergetic treatment was discussed. Genetic modification was also discussed as a potential starch modification for better utilization of starch.